Systematic Literature Review on Financial Constraints and Their Impact on Corporate Innovation - Pratama, Sari Indra; Rosalina, Rita (INDONESIAN JOURNAL OF SUSTAINABILITY, 2025)
Financial constraints are a major obstacle in the corporate innovation process, especially related to limited access to capital for research and development (R&D) investment. This has implications for the company's low innovation capacity and competitiveness in a competitive global market. The purpose of this research is to systematically review the literature related to the influence of financial constraints on corporate innovation, as well as identify the role of public policy and management strategies in overcoming these obstacles. The method used is systematic literature review (SLR) with a qualitative approach, following the PRISMA 2020 guidelines, as well as manual content analysis of selected articles from Scopus indexed journals for the 2024-2025 period. The data consisted of five scientific articles relevant to the keywords "Financial Constraint" and "corporate innovation." The results of the study show that financial constraints limit innovation investment, especially in the context of strict regulations, economic uncertainty, and external risks such as natural disasters. Technology-finance policy interventions have proven effective in reducing financial barriers, while adaptive management and digitalization strategies support innovation continuity. In conclusion, a deep understanding of financial constraints and their mitigation strategies is crucial to encourage sustainable innovation and maintain the company's competitiveness in the global era.